(untitled) (Global Journal of Management and Business Research, 2022)
The purpose of this article is to identify, from a review of the existing literature on Logistics Service Providers (LSPs), the factors that generate the logistics performance of freight or freight carriers.The review of the work of many authors in the field has made it possible to develop a theoretical model on the possible determinants of better logistics performance. This allows us to suggest that the possession of certain logistics resources and skills, as well as capacity building in the management of the transport service, are catalysts on which freight carriers can rely to improve their logistics performance.